Needs Analysis: Social Skills-Based Learning Model For Children With Learning Disabilities at an Inclusive School - Husadani, Rizki; Suryani, Nunuk; Yusuf, Munawir (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to explore the needs of social skills-based learning models for inclusive schools for children with learning disabilities. The research method used was a quantitative descriptive approach. The research subjects were teachers who teach children with learning disabilities in eight inclusive elementary schools in Surakarta. The technique to get the data collection used was a structured questionnaire with Likert scale. Then, it was analyzed using descriptive statistical analysis techniques by categorizing i.e. The analysis results showed that the level of needs of a social skills-based learning model for children with learning disabilities was very high with final percentage of 83%. Therefore, it was necessary to develop a skill-based learning model for children with learning disabilities in an inclusive school to assist teachers in developing social skills for children with learning disabilities.